Teaching a Second Language: How Multi-Lingual Collaboration and Munby’s ‘Needs and Needs Analysis’ Work - Rahman, Md. Atiqur (ABC Journal of Advanced Research, 2019)
This paper deals with the teaching and learning process of English as a second language, especially in the context of Bangladesh where students in any academic institutions like colleges or universities are taught and instructed by teachers supposedly trained and skilled in teaching English as Foreign Language (EFL). It explores how an EFL teacher—using English as the primary mode of instruction—might deploy a methodological combination, where teacher transmission and student collaboration can be used as an effective method to teach this particular content-based subject to non-native English speakers. This methodological procedure is arguably influenced by the teacher’s EFL background having an undeniable effect on students’ input in the lesson, resulting in a syllabus which integrates students’ beliefs as well as experiences regarding the use of language in society and deploying a multilingual collaboration among the students in the lectures themselves. Such a version of traditional lecturing and student interaction, which is termed here as “collaborative dialogue”, has, to some degree, firstly succeeded in raising the general class level of comprehension and, secondly yet more significantly, lowering the general anxieties about interaction in class. Furthermore, it has also resulted in pooling student input about language use to create a rich, contrastive perspective on sociolinguistic topics.